Improvement and Decline in Tactile Discrimination Behavior after Cortical Plasticity Induced by Passive Tactile Coactivation - Hodzic, Amra (J Neurosci, 2004)
Perceptual learning can be induced by passive tactile coactivation without attention or reinforcement. We used functional MRI (fMRI) and psychophysics to investigate in detail the specificity of this type of learning for different tactile discrimination tasks and the underlying cortical reorganization. We found that a few hours of Hebbian coactivation evoked a significant increase of primary (SI) and secondary (SII) somatosensory cortical areas representing the stimulated body parts. The amount of plastic changes was strongly correlated with improvement in spatial discrimination performance. However, in the same subjects, frequency discrimination was impaired after coactivation, indicating that even maladaptive processes can be induced by intense passive sensory stimulation.